The role of androgens in pressure overload myocardial hypertrophy - Schafstedde, Marie; Nordmeyer, Sarah (Frontiers in Endocrinology, 2023)
Pressure overload hypertrophy of the left ventricle is a common result of many cardiovascular diseases. Androgens show anabolic effects in skeletal muscles, but also in myocardial hypertrophy. We carefully reviewed literature regarding possible effects of androgens on specific left ventricular hypertrophy in pressure overload conditions excluding volume overload conditions or generel sex differences.